REFORMA AL ART. 58 DE LA LEY ORGANICA DEL SERVICIO PUBLICO, INCORPORANDO A FAVOR DE LOS SERVIDORES PUBLICOS, LOS DERECHOS CONSTITUCIONALES EN RELACION AL PRINCIPIO DE IGUALDAD ANTE LA LEY, ELIMINANDO AQUELLOS QUE CONSTITUYEN VULNERACION - QUEZADA RIOFRIO, JESSICA ABIGAIL (2016)
The problem of study and research thesis appear in the study of administrative law and specifically within the public law governing the rights and guarantees of civil servants, Law was issued to harmonize with the new currents of constitutional law; and that by studying these contents caught our attention constitutional statements have not been governed by law and therefore the research project was planned and after approval included a table of contents for approval. So in the conceptual framework it produced the analysis of legal institutions of public service and the evolution that has been through the history of public service comprising acts, administrative acts involved. The actions of the civil service as a participant in the civil service are set out in the doctrinal framework and what the effects and services received from the servers are. In the legal framework necessarily solved the analysis of the rights and guarantees of public servants and how they act within the state organization and the superiority of these rules against the law. The study of the Organic Law of Public Service enables us to discover some principles that has limited public 5 services and access to the civil service can analyze the effects this law has produced public employees, and their rights regime disciplinary.Completed the final report conclusions and recommendations allowed us to clarify the reality that they are public servants and also helped us see where the public servants and introduce legal reforms which ratifies the proposal.